The Effects of Engagement on Learning Outcome among Undergraduate Sports Science Students in Ethiopia - Tadesse (PhD), Tefera (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2021)
Despite increased attention paid to student engagement and their learning outcomes in universities in recent years, very little is known about the extent of engagement of undergraduate sports science students and how that is related to their learning outcomes in a university. This study examined the extent of student engagement and student learning outcomes, and further explored the extent of their relationships. A cross-sectional survey design was used. The sample includes volunteered undergraduate sports science students (n = 83)enrolled in four randomly selected public universities in Ethiopia. Quantitative data from the 83 respondents were analyzed using descriptive, bivariate correlations and a 2-steps multiple regression analysis. Findings reveal above average levels of engagement and learning outcome scores, and low to moderate relations between the scores. Both independently and interdependently, the student engagement factors reveal statistically significant relationships with all the measured outcomes, adjusted r2 ranging between 17 and 50% (p < .001). All significant predictors fall within regression coefficients (β) of 22 and 44% (p <.01 and .05 levels). Regression results suggest evidence of differential effects of student engagement on the measured learning outcomes. Implications for practice and suggestions for future research are also considered.